Indigeneity on the move: varying manifestations of a contested concept - Gerharz, Eva; Nasir Uddin; Chakkarath, Pradeep ([s.n.], 2017)
“Indigeneity” has become a prominent yet contested concept in national and international politics, as well as within the social sciences. This edited volume draws from authors representing different disciplines and perspectives, exploring the dependence of indigeneity on varying sociopolitical contexts, actors, and discourses with the ultimate goal of investigating the concept’s scientific and political potential